2017
DOI: 10.1002/lary.26489
|View full text |Cite
|
Sign up to set email alerts
|

Metformin effects on head and neck squamous carcinoma microenvironment: Window of opportunity trial

Abstract: Objective The tumor microenvironment frequently displays abnormal cellular metabolism, which contributes to aggressive behavior. Metformin inhibits mitochondrial oxidative phosphorylation, altering metabolism. Though the mechanism is unclear, epidemiologic studies show an association between metformin use and improved outcomes in HNSCC. We sought to determine if metformin alters metabolism and apoptosis in HNSCC tumors. Study Design Window of opportunity trial of metformin between diagnostic biopsy and resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 75 publications
0
42
0
Order By: Relevance
“…No difference was seen in MCT4 expression [82]. Metformin induced carcinoma cell apoptosis 2.8 fold by TUNEL staining in this trial, which was not seen in control patients and increased lactate levels 2.4 fold in carcinoma cells [82]. This can be viewed as proof of principle that metformin can be used to modify the metabolic milieu of tumor stroma.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…No difference was seen in MCT4 expression [82]. Metformin induced carcinoma cell apoptosis 2.8 fold by TUNEL staining in this trial, which was not seen in control patients and increased lactate levels 2.4 fold in carcinoma cells [82]. This can be viewed as proof of principle that metformin can be used to modify the metabolic milieu of tumor stroma.…”
Section: Discussionmentioning
confidence: 78%
“…Patients who received metformin were found to have increased stromal CAV1 staining intensity, from 25.7% pre-treatment to 62.8% post-treatment; control patients showed no difference in staining. No difference was seen in MCT4 expression [82]. Metformin induced carcinoma cell apoptosis 2.8 fold by TUNEL staining in this trial, which was not seen in control patients and increased lactate levels 2.4 fold in carcinoma cells [82].…”
Section: Discussionmentioning
confidence: 94%
“…Apoptotic cells were identified using the TUNEL-based ApopTag Peroxidase In Situ Apoptosis Detection Kit (MilliporeSigma, Burlington, MA) as previously described 30 .…”
Section: Methodsmentioning
confidence: 99%
“…A single study has examined the role of metformin in head and neck squamous cell carcinoma (HNSCC) prior to surgery, with change in stromal caveolin-1 (CAV1) and monocarboxylate transporter 4 (MCT4) as the primary endpoint, with the rationale that metformin targets cells with altered glycolysis, which has been shown in cancer-associated fibroblasts particularly in HNSCC [59]. Low CAV1 and increased MCT4 levels are associated with aggressive disease in HNSCC.…”
Section: Reported Clinical Trialsmentioning
confidence: 99%
“…Low CAV1 and increased MCT4 levels are associated with aggressive disease in HNSCC. The study showed a significant increase in CAV1 but no change in MCT4 in 33 evaluable participants between baseline biopsy and surgical specimen [59]. …”
Section: Reported Clinical Trialsmentioning
confidence: 99%